Human Capital and Partnership To Achieve of Sustainable Competitive Advantage in Micro and Small Business. - Mardatillah, Annisa; Raharja, Samun Jaja; Hermanto, Bambang; Herawaty, Tety (International Journal of Supply Chain Management, 2020)
Abstract The purpose of this study is to analyze the effect of human capital and partnership to achieve sustainable competitive advantage in micro and small businesses. The findings of this study contribute to the development of the concept of resource-based view theory to achieve sustainable competitive advantage. This is in line with the thought of resource-based view that human capital and partnerships are intangible resources of a company that will determine whether a company can sustainable competitive advantage. However, previous research can not answer the research gap on human capital and partnerships to achieve sustainable competitive advantage. This research answers the gap by testing human capital and partnerships to achieve sustainable competitive advantage. High heterogeneity of the company's resources will provide a sustainable competitive advantage because it is more valuable, rare, inimitable, non-substitutional. The data analysis of this research used the Structural Equation Model with the Partial Least Square program. Keywords: Human Capital, Partnership, Sustainable Competitive Advantage, Micro and Small Enterprise